Answer:
x = 5 and y = -2
Step-by-step explanation:
Here you have given what y is equal to, this means you can sub this into the first equation:
3x - 2(x - 7) = 19
Expand the brackets:
-2 * x = -2x
-2 * -7 = 14
3x -2x +14 = 19
Move the +14 over to the other side making it a -14:
3x - 2x = 19 - 14
3x - 2x = 5
3x - 2x = x
So x = 5
Now sub this into the first equation:
3(5) - 2y = 19
15 - 2y = 19
Move the -2y over to the other side making it a +2y, and move the +19 over to the other side making it a -19:
15 - 19 = 2y
-4 = 2y
Divide both sides by two:
y = -2
So x = 5 and y = -2